Z-Source Inverter for General Purpose Drives in Motoring and Regenerating Operation - Sack, Lothar; Piepenbreier, Bernhard; von Zimmermann, Moritz (SPEEDAM 2008, 2008)
Due to rising energy costs and environmental aspects, high efficiency of electric drives is increasingly considered to be very important. Unfortunately, the efficiency of induction motors is very badly affected if terminal voltage is lowered. Unintentional undervoltage can be avoided regardless of its cause by means of the step-up effect of the Z-source inverter. The paper describes the selection of the components of the Z-source converter and a principle for operation with reduced stress to the components. The paper emphasizes the relevance of the output to input voltage ratio and of the DC link eigenfrequency for the installation size of the passive and active components. A presented design procedure for optimized throughput of power uses a DC equivalent circuit and leads to minimized passive components. With this set of parameters, further characteristics of electric and thermal stress of the components can be determined analytically and by simulation. The paper comprises design formulas in general form and their evaluation for an experimental test set-up for a 7.5 kW three-phase standard motor in motor and regenerative operation. ©2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEEAS.zsourc
Keywords: Drive; Regenerative braking; Z-sourced inverter